Affirmative Action Policies and the Constitution - Shad Saleem Faruqi (Kajian Malaysia, 2003)
Equality before the law is one of the greatest of all constitutional ideals. But in a world of inherent disparities between the rich and the poor, the educated and the illiterate, the privileged and the powerless, the conferment of formal equality does not secure functional parity. Equality amongst unequals favours the strong over the weak and acts powerfully to maintain the stafus quo. In an untrammelled market economy, wealth, power and position tend to gravitate towards the privileged few. The declaration of formal, legal equality becomes an empty legal formula in the face of massive economic, social and educational disparities. A commentator once observed that there is no greater inequality than the equal treatment of unequals.